Karakteristik Kimia dan Fisik Bubur Instan Berbahan Dasar Tepung Jagung Pulut dan Tepung Kacang Merah - Palijama, Syane; Breemer, Rachel; Topurmera, Miranda (AGRITEKNO: Jurnal Teknologi Pertanian, 2020)
People tend to choose their food practically and efficiently presented and made without reducing their nutritional content. The use of red bean flour is needed to replace protein sources while waxy rice flour contributes to carbohydrate replacement. The purpose of this study was to know and to determine the characteristics of instant porridge with the ratio of red bean flour and waxy corn flour. Results showed that the characteristics of instant porridge were influenced by the different ratios between red bean and waxy corn flour on instant porridge ash, protein, fat, fiber, carbohydrate contents as well as ask bulk density and rehydration powder. The ratio between corn and red bean flours of 80% and 20% resulted in instant porridge with moisture, protein, and carbohydrate of 3.44%, 10.8%, and 80.53%, respectively and met the quality standard set by SNI 01-7111.4-2005, an ash content of 1%, a fat content of 0.76% the fiber content of 3.79%, bulk density of 1.03 g/mL, and rehydration power of 2.83 mL/g.: instant porridge, the ratio of red bean, and waxy flour. Keywords: instant porridge, the ratio of red bean and waxy cornflour ABSTRAK Masyarakat lebih memilih makanan yang dikonsumsi secara praktis dalam bentuk penyajian maupun dalam pembuatannya tanpa mengurangi pemenuhan kebutuhan gizi. Penggunaan tepung kacang merah diperlukan sebagai sumber protein dan penggunaan tepung jagung pulut sebagai pengganti karbohidrat. Tujuan dari penelitian adalah untuk mengetahui dan menentukan karakteristik bubur instan dengan rasio tepung kacang merah dan tepung jagung pulut. Hasil penelitian menunjukan bahwa karakteristik bubur instan dipengaruhi oleh rasio tepung kacang merah dan tepung jagung pulut yang berbeda terhadap kadar air, kadar abu, kadar protein, kadar lemak, kadar serat, kadar karbohidrat, densitas kamba dan daya rehidrasi. Hasil penelitian menunjukkan rasio tepung jagung pulut 80% dan tepung kacang merah 20% memiliki karakteristik kadar air (3,44%), kadar protein (10,8%) dan kadar karbohidrat (80,53%) sesuai SNI 01-7111.4-2005, kadar abu (1%), kadar lemak (0,76%), kadar serat (3,79%), densitas kamba (1.03 g/mL) dan daya rehidrasi (2.83 mL/g). Kata kunci: bubur instan, tepung jagung pulut dan tepung kacang merah